Odpowiedzi

2010-01-03T15:43:08+01:00
5x(x-2)-x(x-2)<-4=
5x² -10x - x² + 2x < -4
4x² - 8x < -4
4x² - 8x + 4 < 0

delta rowna sie b²- 4ac
8² - 4 * 4 * 4
64 - 64
0

x1 rowna sie -b - delta / 2a
8-0 / 2* 4
8 / 8
1
x1 rowna sie 1

x2 rowna sie -b + delta / 2a
8+0 / 2*4
8/ 8
1
x2 rowna sie 1

2-(x-3)≥0,5x-1
2 - x - 3 ≥ 0.5x - 1
-x - 0,5x ≥ -1 -2 +3
- 1,5x ≥ 0

x(2-x)+(x+2)(x-2)>2
2x - x ² + x² + 2x + 2x - 4 >2
6x - 4 >2
6x > 2 +2
6x > 4 /6
x > 4/6



(x-3)(x+3)-(x-2)²≤19
x² +3x -3x -9 - (x-2)(x-2) ≤19
x² - 9 - (x² - 2x - 2x + 4) ≤19
x² - 9 - x ² + 2x + 2x - 4 ≤19
- 13 + 4x ≤19
4x ≤19 + 13
4x ≤ 32
x ≤ 32 / 4
x ≤ 8
2010-01-03T15:52:19+01:00
=5x-2x-(2x)<-4=5x-2x+2x=5x
=2-(-3x)>1,05x=2+3x>1,05=3x-1,05x>2=1,95>2
=x-2x+2x-2x>2=x>2
=(x-3)(x+3)-(x-4)<19=-3x+3x-(4x)<19=-4x<19